"Fantasía en 6/8", the story of one bambuco through the history of bambuco (2016)
As part of the application of the hermeneutical circle to musical interpretation, a methodological proposal raised from the qualitative interpretive perspective, this article of reflection, derived from the research, seeks to expand the historical and compositional horizon of the Bambuco Fantasy in 6/8 of the Colombian composer José Revelo Burbano. To achieve this goal, an approximation is made to the general characteristics of the historical evolution of the bamboo and the information on the compositional context of the work is expanded with an interview with the composer. It is expected to contribute to knowledge about hermeneutics as a tool for musical interpretation, as well as to the reference to traditional Colombian music, especially the original Colombian musical repertoire for clarinet and guitar, by enriching the interpretative possibilities of the work analyzed from of the meaning and meaning of its history.